2015
DOI: 10.1016/j.nutres.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Oat consumption reduced intestinal fat deposition and improved health span in Caenorhabditis elegans model

Abstract: In addition to their fermentable dietary fiber and the soluble β-glucan fiber, oats have unique avenanthramides that have anti-inflammatory and antioxidant properties that reduce coronary heart disease in human clinical trials. We hypothesized that oat consumption will increase insulin sensitivity, reduce body fat, and improve health span in Caenorhabditis elegans through a mechanism involving the daf-2 gene, which codes for the insulin/insulin-like growth factor-1–like receptor, and that hyperglycemia will at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
2
18
0
1
Order By: Relevance
“…Our results showed no change in lifespan with sucrose. Glucose increased intestinal fat deposition and reduced the lifespan in C. elegans which is consistent with previous studies (Zheng et al, 2014, Gao et al, 2015a). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed no change in lifespan with sucrose. Glucose increased intestinal fat deposition and reduced the lifespan in C. elegans which is consistent with previous studies (Zheng et al, 2014, Gao et al, 2015a). …”
Section: Discussionsupporting
confidence: 93%
“…Lifespan was reduced in the glucose treated group as previously reported (Lee et al, 2009, Gao et al, 2015a, Gao et al, 2015b). Here we report a biphasic effect of fructose increasing lifespan at lower doses and shortening lifespan at a higher dose.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported previously that some legumes such as red, black and marine beans act on longevity and as fat reducers [46]. As well as the use of legumes, it has been shown that oats, a nutritionally rich cereal, can also prolong life and reduce fat [47]. It provides antioxidant, anti-inflammatory and anti-angiogenic properties, and its consumption introduces a lowcalorie intervention through caloric dilution, as well as lowering lowdensity lipoprotein cholesterol, reducing body fat and risk factors for coronary disease [48][49][50][51][52][53].…”
Section: Mammals E Caenorhabiditis Elegansmentioning
confidence: 99%
“…Plant proteins are gaining considerable interest as food ingredients with respect to the latest trends towards a healthy lifestyle, vegetarianism and veganism. Modern lifestyle‐related chronic diseases such as obesity, insulin resistance and diabetes are the health challenges of the 21 st century . As a result, the food industry aims to develop functional foods and functional food ingredients (for example, probiotics and plant‐derived proteins), which exert positive effects on the health and wellbeing of consumers.…”
Section: Introductionmentioning
confidence: 99%